One bread, one body, one church essays on the 'Ecclesia' of Christ today in honor of Bernard P. Prusak - Cimorelli, Christopher 1983- (Annua nuntia Lovaniensia, 2021)
How does the church come from Jesus?" Previously, this was a much clearer and more settled question. It could be answered from dogmatic conclusions, rather than from historical investigation. Since the methodological revolutions in Catholic theology of the twentieth century that initiated hermeneutical processes of self-discovery, potential answers to this question are far less stable and comprehensive. The recovery of past elements of tradition and the uncertainty of the future demand creative answers to the challenges facing the church regarding its identity. This volume, prepared in honor of Bernard P. Prusak, attempts to constructively explore the question of ?how? the church comes from Jesus. The contributors have provided critical reflections from different theological disciplines in order to think this question anew from a more ?synoptic? perspective in line with Prusak?s own theology. His work consistently plumbs the depths of Christian history and traditions, alive to the liturgical and sacramental life of the Body of Christ, to address the concerns of Christians seeking understanding of their faith today.